Plaque Components in Symptomatic Moderately Stenosed Carotid Arteries Related to Cerebral Infarcts. Issue 2 (February 2015) - de Rotte, Alexandra A.J.; Truijman, Martine T.B.; van Dijk, Anouk C.; Liem, Madieke I.; Schreuder, Floris H.B.M.; van der Kolk, Anja G.; de Kruijk, Jelle R.; Daemen, Matt J.A.P.; van der Steen, Anton F.W.; de Borst, Gert Jan; Luijten, Peter R.; Nederkoorn, Paul J.; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— Carotid plaque composition is a major determinant of cerebrovascular events. In the present analysis, we evaluated the relationship between intraplaque hemorrhage (IPH) and a thin/ruptured fibrous cap (TRFC) in moderately stenosed carotid arteries and cerebral infarcts on MRI in the ipsilateral hemisphere. Methods— A total of 101 patients with a symptomatic 30% to 69% carotid artery stenosis underwent MRI of the carotid arteries and the brain, within a median time of 45 days from onset of symptoms. The presence of ipsilateral infarcts in patients with and without IPH and TRFC was evaluated. Results— IPH was seen in 40 of 101 plaques. TRFC was seen in 49 of 86 plaques (postcontrast series were not obtained in 15 patients). In total, 51 infarcts in the flow territory of the symptomatic carotid artery were found in 47 patients. Twenty nine of these infarcts, found in 24 patients, were cortical infarcts. No significant relationship was found between IPH or TRFC and the presence of ipsilateral infarcts. Conclusions— MRI detected IPH and TRFC are not related to the presence of old and recent cortical and subcortical infarcts ipsilateral to a symptomatic carotid artery stenosis of 30% to 69%. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01208025.